The Nation Form in the Global Age Ethnographic Perspectives - Ahmad, Irfan; Kang, Jie (Global Diversities, 2022)
This open access book argues that contrary to dominant approaches that view nationalism as unaffected by globalization or globalization undermining the nation-state, the contemporary world is actually marked by globalization of the nation form. Based on fieldwork in Africa, Asia, Europe and the Middle East and drawing, among others, on Peter van der Veer's comparative work on religion and nation, it discuss practices of nationalism vis-a-vis migration, rituals of sacrifice and prayer, music, media, e-commerce, Islamophobia, bare life, secularism, literature and atheism. The volume offers new understandings of nationalism in a broader perspective. The text will appeal to students and researchers interested in nationalism outside of the West, especially those working in anthropology, sociology and history.